Multigravida 14 weeks pregnant with hematemesis + electrolyte imbalance: Multigravida 14 weeks pregnant with hematemesis + electrolyte imbalance - Fonda Octarianingsih Shariff; norma estarina (Medula, 2026)
A 34-year-old multigravida patient 7 weeks pregnant came to the emergency room of RSPBAH Bandar Lampung with complaints of nausea and vomiting since 2 weeks ago. With compaints of nausea (+),for two months, recently vomiting, accompanied by fresh blood clots. Vomiting today 15times and vomiting accompanied by fresh blood and blood clots >4 times. Hearthburn, headache, weekness vital signs of blood pressure 120?80mmhg, pulse100x/minute, temperature 36,3 c, respiratory rate 20x/minute, axogen saturation 97%, in the hematology supporting examination on 05-09-2024 found a decrease in Hit, Type of Leukocyte Rod 0%, Hit. Type of Leukocyte Lymhocyte 19%, and MCH which increase to 32pg. And the supporting examination of Ultrasonography (USG) obtained the impression of a signle fetus alive with a gestasional age 14 weeks, Estimated delivery on February 26,2024. Biparietal Diameter with assize of 2.95cm. The diagnosis in this case is a 14 week pregnant with Hematemesis + Electrolyte Imbalance. The management obtained in this patient is observation of general condition, periodic vital sign examination, indication of hospitalization with treatment : observation of vital sign and GCS, advise the mother to rest in bad, IUVD RL XXtpm, Ondancentron Injection 3x1, Ranitidine 2x1, Antasid syr 3x1. The Prognosis In this patient is dubia ad bonam.